The influence of sitting work position and sitting time for the risk of hemorrhoid in female production workers at the hand-rolled cigarette factory - Izzatul Abadiyah; Dewi Sumaryani Soemarko; Herqutanto2; Suryo Wibowo; Ambar Roestam (ILUNI MKK FKUI and PRODI MKK FKUI, 2021)
Introduction: According to medical check up results of the hand-rolled cigarette factory PT. X in 2018, a hemorrhoid prevalence of 33% was found. Several studies have tried to show an association between individual factors such as age, family history, constipation, obesity, pregnancy, fiber consumption, and defecation position in research subjects in clinics and hospitals. Nevertheless, the effects of sitting work position and sitting time on the risk of hemorrhoid is yet to be revealed. This study aims to prove the effect of these factors on the increased risk of hemorrhoids. Methods: An observational study with a 1:1 unmatched case control design with 300 female workers as subjects. The risk factors related with hemorrhoids were obtained from primary and secondary data. Cases were workers diagnosed with hemorrhoids and controls were workers who were not diagnosed with hemorrhoids during a medical check-up 2018. Data analysis was performed using univariate and bivariate analysis. Results: The mean ages of the subjects were 42.49±3.05 years old (cases) and 42.83±3.02 years old (controls), with most education level was a junior high school in both groups. Bivariate analysis pointed out that sitting work position and sitting time did not have a significant relationship with the incidence of hemorrhoids. Meanwhile, consumption of less fruit (OR=3.84;95%CI 1.87-7.91) and less vegetable (OR=2.41;95%CI 1.36-4.28) increased the risk of hemorrhoid compared to sufficient vegetables and fruit consumption. Conclusion: Sitting work position and sitting time were not associated with an increased risk of hemorrhoids. Meanwhile, consumption of less vegetable and fruit increased the risk of hemorrhoids.